Analisis Variasi Jumlah Sudu Terhadap Torsi Yang Dihasilkan Pada Turbin Vortex - Aswanto, Trio Harinaldi; Purwantono, Purwantono; Putra, Randi Purnama; Afnison, Wanda (Asian Journal of Science, Technology, Engineering, and Art, 2023)
Water turbines, particularly vortex turbines, represent a promising alternative energy source with significant potential for development. Vortex turbines are a relatively novel type of water turbine, offering ample opportunities for further research. This study aims to assess the efficiency of different blade variations, specifically 3, 4, and 5 blades. Computational Fluid Dynamics (CFD) analysis was conducted using Solidworks 2022 software. The simulation results indicate that the torque values for 3 blades, 4 blades, and 5 blades were 0.26 Nm, 3.02 Nm, and 4.96 Nm, respectively. Efficiency calculations were performed using a formula, yielding efficiencies of 0.9% for 3 blades, 11.91% for 4 blades, and 20.74% for 5 blades. These results suggest that higher blade counts lead to greater efficiency.